The Black Balloon - Down, Elissa; Rhys Wakefield; Luke Ford; Toni Collette; Erik Thomson; Gemma Ward; Lloyd AllisonYoung; Nathin Butler; Lisa Kowalski; Firass Dirani; Aaron Glennane; Andy Meritakis; et al. (Australia Australian Film Commission, 2008)
All Thomas wants is a normal adolescence but his autistic brother, Charlie, thwarts his every opportunity. Will Thomas, with the help of his girlfriend, Jackie (Ward), accept his brother?
Language: English Subtitle: Turkish
Keywords: Drama